2015
DOI: 10.1049/el.2015.1545
|View full text |Cite
|
Sign up to set email alerts
|

Design of validation experiment for analysing impacts of background ionosphere on geosynchronous SAR using GPS signals

Abstract: Geosynchronous synthetic aperture radar (GEO SAR) is susceptible to the ionosphere due to its ultra-long integration time and ultra-wide coverage, resulting in image defocusing and drift. A design of a validation experiment for analysing ionospheric impacts on GEO SAR focusing using global position system (GPS) signals is presented. The experiment consists of data acquisition and equivalent pre-processing of the GPS signals, along with the following contaminated GEO SAR signal modelling, imaging and evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It has been indicated that the presence of correlated Gaussian noise was employed to characterize the ionospheric temporaldecorrelation in GEO SAR system [8]. Polynomial approximation was applied to analyze the effect of temporal variations of the background ionosphere [9][10][11][12]. Based on this method, an in-depth analysis of the temporal variation of the background ionosphere on GEO SAR imaging was conducted [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the presence of correlated Gaussian noise was employed to characterize the ionospheric temporaldecorrelation in GEO SAR system [8]. Polynomial approximation was applied to analyze the effect of temporal variations of the background ionosphere [9][10][11][12]. Based on this method, an in-depth analysis of the temporal variation of the background ionosphere on GEO SAR imaging was conducted [13].…”
Section: Introductionmentioning
confidence: 99%
“…Related research is focused on the system design and optimization [ 5 , 6 , 7 , 8 ] and the development of accurate imaging algorithms [ 9 , 10 ]. Other studies are devoted to the non-ideal influences, including atmospheric effects [ 11 , 12 , 13 , 14 ]. However, orbital perturbations are rarely concerned, though satellites are certain to be impacted by perturbations caused by the Earth’s non-spherical mass distribution, the atmospheric drag, the third body attraction, the solar radiation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Methodology description: It is a double loop body for the computer realisation as to each azimuth point and pixel in the scene, and the IPP coordinate should be calculated each time for indexing the relevant STF. Moreover, due to the ultra-long synthetic aperture time and ultralarge observation scope of the GEO SAR, it is more computationally intensive and difficult for the computer realisation, compared with the low-Earth-orbit system [7]. Thus, we do need an efficient and accurate simulation method to generate the scintillation-affected L-band GEO SAR raw data.…”
mentioning
confidence: 99%
“…where r ′ T = ct{r T }/2 represents the slant range segment in echo domain that just consists of the variation of the real slant range on account of the image pixel line in each azimuth point. Note that, 1 1 ; 1 2 ( ] is the variation of 1 1 with the fixed 1 2 in (6) and (7). Therein, V i is a complex interpolator that maps the slant range r 0 of the grid line into the pixel value I; V y is a real interpolator that maps r 0 into the IPP across-track coordinate y (the IPP along-track abscissa x is fixed as to each azimuth point h a and each pixel line t 0 ), which is utilised to modulate the two-way STF on the SAR signal with a nice accuracy; V r indicates a real interpolator mapping the real slant range r T of the image pixel line into r 0 .…”
mentioning
confidence: 99%